Efektivitas Model Blended Learning pada Pendidikan Abad ke-21: Literature Review - I Wayan Karmana (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
This study aims to examine the effectiveness of blended learning models in supporting 21st century education through a literature review approach. The method used is a literature review with a qualitative descriptive approach to scientific articles published in 2019–2025 and obtained from various databases, such as Google Scholar, Scopus, ERIC, ScienceDirect, and Garuda. The analysis process is carried out through identification, selection, analysis, and synthesis of research results based on the inclusion and exclusion criteria that have been set. The results of the study show that blended learning is generally effective in improving learning outcomes, motivation, independence, and student involvement. In addition, this learning model contributes to the development of 21st century skills, such as critical thinking, problem-solving, collaboration, communication, creativity, and digital literacy. The effectiveness of the implementation of blended learning is influenced by various factors, including the readiness of technology infrastructure, the digital competence of educators and students, the quality of learning design, and institutional support. This study also identified research gaps related to the long-term impact of blended learning on higher thinking skills, character building, creativity, and readiness for the world of work. Thus, blended learning can be recommended as a relevant learning strategy in supporting educational transformation in the digital era, provided that its implementation is designed in a systematic, balanced, and student-centered manner.